The Impact of Luther and the Reformation in the Portuguese Seaborne Empire: Asia and Brazil, 1520–1580 - Paiva, José Pedro (The Journal of Ecclesiastical History, 2019)
This article assesses how Lutheran and other Reformation doctrines spread and were countered in the Portuguese seaborne empire. Portugal's inquisitorial and episcopal repression of ‘Lutherans’ was extended to Brazil and Asia, where it was supported by the Society of Jesus. The Portuguese empire's transcontinental connections favoured the emergence of interconnected histories, facilitating the circulation of books, engravings and beliefs and thus provided non-Portuguese people with links to the reformed world that spread amongst and disturbed the Portuguese living in India and Portuguese America. By opening up routes the Portuguese, paradoxically, functioned as vectors for other ways of interpreting Christianity.